MOISTURE REGIME CALCULATION FOR SINGLE-LAYER ENCLOSING STRUCTURES USING DISCRETE-CONTINUAL MATHEMATICAL MODEL - Vladimir G. Gagarin (International Journal for Computational Civil and Structural Engineering, 2018)
The paper describes moisture regime calculation for single-layer enclosing structures using discrete-continual method. A formula for calculation of moisture potential dependence on time in any enclosing structure section, at any time, under continuous control for temperature distribution, has been derived. Moisture regime calculation results under the proposed method have been compared to results obtained by well-known methods by V.G. Gagarin and V.V. Kozlov for aerated concrete single-layer enclosing structure. It has been found out that the proposed method gives quantitative and qualitative results similar to results obtained using Gagarin’s unsteady-state method.